The North Pacific Program: A Pedagogical Pattern, A Specific Theme: Leadership - John Curtis Perry (Tufts Archival Research Center, 2020)
The North Pacific Program: A Pedagogical Pattern, A Specific Theme: Leadership, 1993 Summer Seminar